2012
DOI: 10.1029/2012jd017508
|View full text |Cite
|
Sign up to set email alerts
|

Climate response of the South Asian monsoon system to anthropogenic aerosols

Abstract: [1] The equilibrium climate response to the total effects (direct, indirect and semi-direct effects) of aerosols arising from anthropogenic and biomass burning emissions on the South Asian summer monsoon system is studied using a coupled atmosphere-slab ocean model. Our results suggest that anthropogenic and biomass burning aerosols generally induce a reduction in mean summer monsoon precipitation over most parts of the Indian subcontinent, strongest along the western coastline of the Indian peninsula and east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
141
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(153 citation statements)
references
References 93 publications
(138 reference statements)
10
141
2
Order By: Relevance
“…Given the neglect of aerosol forcing in PLASIM-ENTS, this JJA cooling in south-east Asia should not be regarded as robust; aerosols are an important forcing of the south-east Asian monsoon through a range of likely competing effects (-see e.g. (Ganguly et al, 2012).…”
Section: Climate Model: Plasim-entsmentioning
confidence: 99%
“…Given the neglect of aerosol forcing in PLASIM-ENTS, this JJA cooling in south-east Asia should not be regarded as robust; aerosols are an important forcing of the south-east Asian monsoon through a range of likely competing effects (-see e.g. (Ganguly et al, 2012).…”
Section: Climate Model: Plasim-entsmentioning
confidence: 99%
“…However, atmosphere-ocean coupled models often need multicentury simulations to take into account the slow response of SSTs (Danabasoglu and Gent, 2009). The coupled atmosphere slab ocean model by Ganguly et al (2012) shows a mix response of precipitation distribution on the climate scale. It shows a reduction in precipitation over the western coast line of the Indian peninsula and an increase over northwestern part of Indian subcontinent.…”
Section: Impact On Temperature Circulation and Precipitationmentioning
confidence: 99%
“…However, there are a few studies reporting the impacts of carbonaceous aerosols on precipitation over India (Meehl et al, 2008;Wang et al, 2009;Ganguly et al, 2012) and China (Guo et al, 2013(Guo et al, , 2015. Since convective transport (during the monsoon season) inter-links tropospheric processes with the UTLS (Randel et al, 2010;Vogel et al, 2011Vogel et al, , 2015Fadnavis et al, 2013), it is essential to understand impacts of boundary layer emissions on the UTLS.…”
Section: Introductionmentioning
confidence: 99%
“…This was done to avoid the inclusion of extreme orographic precipitation as well as retrieval error in the satellite products (e.g., lower sensitivity over brighter land surfaces for MODIS aerosol products). The ISMR has previously been extensively studied by several investigators (Bollasina et al, 2011;Goswami et al, 2006;Sengupta et al, 2013) as the rainfall variability over this re- gion is highly correlated with that of the entire Indian rainfall during June to September (Gadgil, 2003). Generally, aerosol loading over the ISMR is very high (climatological mean AOD of 0.56, Fig.…”
mentioning
confidence: 99%
“…Lau and Kim (2006) have shown that an aerosol-induced atmospheric heating over Himalayan slopes and the Tibetan Plateau during the monsoon onset period intensifies the northward shift of the Indian summer monsoon, causing a reduction in rainfall over the Indian summer monsoon region (ISMR). On the other hand, a high aerosol loading also induces a solar dimming (absorbing) effect at the surface (Ramanathan and Carmichael, 2008;Ramanathan et al, 2001), which can alter the land-ocean thermal gradient and weaken the meridional circulation, resulting in a drying trend in seasonal rainfall during the Indian summer monsoon (Bollasina et al, 2011;Ganguly et al, 2012). The present of higher concentrations of absorbing aerosols over northern India is shown to induce a stronger northsouth temperature difference, which fosters an enhancement in moisture convergence from the ocean and a transition of a break spell of the Indian summer monsoon (ISM) into an active spell of ISM (Manoj et al, 2011).…”
mentioning
confidence: 99%